Media Sosial antara Hegemoni dan Emansipasi : Tinjauan Kritis terhadap Peran Edukatif dalam Demokrasi Digital - Aris Munandar; Fakih Fadilah Muttaqin; Endang Susanti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aims to explore the role of social media in Indonesia's digital democracy, by highlighting the tension between its function as a tool of hegemony or a means of emancipation. The background of this study is the increasing use of social media by political actors and civil society in voicing, shaping or criticizing public narratives ahead of the 2024 elections. This study uses a critical qualitative approach with a descriptive study design, and applies the Critical Discourse Analysis method and netnographic observation of political content on three main platforms: Twitter, TikTok, and Instagram. Data was collected through literature studies, digital documentation, and observation of user interactions in digital political campaigns. The results show that the digital space is dominated by hegemonic actors such as political elites, partisan buzzers, and platform algorithms that reinforce certain narratives. However, there are also spaces of emancipation formed by digital communities and independent content creators who use social media as a means of political education and symbolic resistance. Counter-narratives that emerge tend to be temporary and are often limited by distribution and visibility controls. These findings have important implications for the development of more critical and participatory digital literacy policies. In addition, this study contributes to the enrichment of critical communication theory, by affirming the importance of viewing social media as a complex pedagogical and ideological field in contemporary democratic practice.